A case of inflammatory myopathy with anti‐PM/Scl antibodies myopathologically presenting as polymyositis with mitochondrial pathology. Issue 5 (22nd July 2020) - Matsumoto, Arifumi; Izumi, Rumiko; Sugeno, Naoto; Suzuki, Naoki; Namatame, Chihiro; Soga, Temma; Nishiyama, Ayumi; Kuroda, Hiroshi; Aoki, Masashi; Nagano, Isao
Abstract: We describe a rare case of inflammatory myopathy with anti‐PM/Scl antibodies myopathologically presenting as polymyositis with mitochondrial pathology (PM‐Mito). A 74‐year‐old Japanese man developed only slowly progressive proximal dominant muscle weakness and atrophy of the four extremities over the past 3 years. His serum creatine kinase level was moderately elevated, and anti‐PM/Scl‐75 antibodies were present. Systemic sclerosis and other systemic autoimmune diseases were not detected. Muscle biopsy revealed endomysial CD8‐positive T‐cell infiltration with diffuse upregulation of major histocompatibility complex class I antigens, few necrotic and regenerative changes atypical for polymyositis, few rimmed vacuoles and protein aggregates atypical for sporadic inclusion body myositis, and an excess of cytochrome C oxidase‐negative muscle fibers reflecting mitochondrial dysfunction. The elevated serum creatine kinase level decreased to the normal range following the initiation of oral tacrolimus treatment. PM‐Mito should be considered as one of the background myopathologies of inflammatory myopathy with anti‐PM/Scl antibodies.